1996
DOI: 10.1159/000291978
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Cytokeratin 19 Fragments in Cervical Cancer

Abstract: Serum levels of a cytokeratin 19 fragment, Cyfra 21–1, were measured using an immunoradiometric assay in 33 women before initial treatment and in 8 women with recurrent tumor. The serum level of Cyfra 21–1 was significantly increased in women with tumors of advanced stage (FIGO) and those with recurrence. The incidence of positivity for Cyfra 21–1 tended to increase with tumor spread. Compared with squamous cell carcinoma (SCC) antigen, the sensitivity of Cyfra 21–1 was comparable to that of SCC antigen. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…Other authors have similarly reported results that are in agreement with the above result (6,7). In our study, we were able to observe similar results in that the pre-treatment value sensitivity for recurrent disease for SCC alone was increased to 90.6% when both tumor markers were employed.…”
Section: Discussionsupporting
confidence: 93%
“…Other authors have similarly reported results that are in agreement with the above result (6,7). In our study, we were able to observe similar results in that the pre-treatment value sensitivity for recurrent disease for SCC alone was increased to 90.6% when both tumor markers were employed.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, serum elevations have also been reported in SCLC [29,44,117,118,167], breast [45,128], ovarian [51], cervical [18,119,129,179], nasopharyngeal [26,99,172,191], esophageal [20,193], gastric [127], bladder [168] and cholangiocellular cancer [181]. In many of these cancers, an association with stage was observed [10,13,18,20,29,[43][44][45]51,91,92,[117][118][119][127][128][129]133,140,167,168,172,179,181,191,193]. Non-malignant causes of cytokeratin elevations include renal insufficiency and severe infections with high rates of cell death [14,…”
Section: Cyfra 21-1 Tpa and Tpsmentioning
confidence: 99%
“…Die zwar variable, aber nie komplett fehlende Expression der Heterodime-re 8/18/19, gegen die der in dieser Studie verwendete monoklonale Antikörper gerichtet ist, ist vermutlich für die beobachtete Sensitivität unseres Studienansatzes verantwortlich. Die Heterogenität der Zytokeratinexpression durch Zervixkarzinomzellen ist vermutlich auch der Grund für die fehlende prognostische Relevanz des molekularbiologischen Nachweises von Zytokeratinfragmenten im peripheren Blut [5,30,44,59]. Die Detektion von Tumorzellen durch Human Papilloma Virus (HPV) mRNA-Fragmente könnte zukünftig eine Option zur Erhöhung der Spezifität des Tumorzellnachweises sein [2, 48,58].…”
Section: Originalarbeitunclassified